KAJIAN DESKRIPTIF TERHADAP KETERSEDIAAN DAN AKSEBILITAS ASET PENGHIDUPAN PETANI SWADAYA KELAPA SAWIT DI KELURAHAN TERAWAS - Wijaya, Cindy Aulia Putri; Wildayana, Elisa; Lifianthi, Lifianthi (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2025)
This study examines the availability and accessibility of livelihood assets of oil palm independent smallholders in Terawas Village, Musi Rawas Regency. Indonesia as a major producer of palm oil faces challenges in increasing the productivity of independent smallholders who are often hampered by limited capital, technology and education. The method used was descriptive qualitative with data collection through surveys and interviews. Results show that although smallholders have adequate land ownership and education levels, they still experience difficulties in accessing financial and social assets. Analysis using the Sustainable Livelihood Framework identified five livelihood assets: human, natural, financial, physical and social. The findings highlight the need for empowerment strategies that focus on improving access to capital and technology, as well as developing farmers' skills. This research is expected to serve as a basis for policies and programs that are more suited to local needs, in order to improve the sustainability of oil palm farming in the area.